PRELIMINARY RE-OS ISOTOPIC DATA IN PGE RICH CHROMITITE LAYERS OF LUANGA ULTRAMAFIC LAYERED INTRUSION – CARAJAS (PARÀ STATE), BRAZIL - Teixeira, Ciro; Ferrario, Alfredo; Girardi, Vicente A.V.; Grieco, Giovanni; Moroni, Marilena (Ofioliti, 1999)
The Luanga layered complex intruded a greenstone belt sequence (Rio Novo Formation) at 2760 Ma (Rb-Sr radiometric dating; Suita and Nilson, 1991). This age is confirmed by relationships with the Lower Proterozoic age of the covering sequence (Salobo and Rio Fresco Units). Lithostratigraphic data based on outcrops and three drillholes confirm the layered nature of the intrusion made up of dunite, peridotite, pyroxenite, norite and gabbro layers from the bottom to the top. Chromitite layers and seams, occur in three well defined horizons located in plagioclase pyroxenites and at the transition zone between dunite and peridotite. The massive chromitite layers show thicknesses between 2 m and a few centimetres. The massive chromitite displays an equigranular texture, with single grains ranging from 0.5 to 2 mm in size. The fresh chromitite layers show: atoll-like texture with olivine and orthopyroxene inside and outside chromite rings, pseudomyrmekitic intergrowth of silicates and chromite. Relationships of the two dominant PGMs (braggite and sperrylite) with the silicates and chromite suggest that PGM crystallization predates the almost contemporaneous precipitation of silicates and chromite. Weathering processes changed only in part the primary composition and mineralogy of the chromitite, for this reason it was possible to select well preserved primary minerals and mineral assemblages for analyses with microprobe, fire assay and neutron activation and mass spectrometry. The chemistry of the chromitite layers is typical of chromites generated by fractionation and cumulus processes, with widely ranging, but generally high Al2O3 and low Cr2O3 contents. PGE chondritic profiles display a PPGE enrichment in all the three horizons (Table 1), (Diella et al., 1995).Preliminary Re–Os isotopic data were obtained on two selected massive chromitite samples from the PGE richer (Lu3) and the relatively PGE poorer (Lu 6) chromitite horizons. These two samples show respectively the highest and the lowest PGE contents of all data collected.Isotopic analyses were performed with the Carius tube isotope dilution procedure, using the PGE standard “WPR- 1” provided by the Canadian Certified Reference Materials Project.Isotopic data (Table 2), in form of 187Os/188Os, were transformed into 187Os/186Os by using a 188Os/186Os ratio of 8,302 (Luck and Allegre, 1983). Initial 187Os/186Os ratios and gOs were determined by considering an age of emplacement of Luanga complex at 2700 Ma. Reliabilty of data is confirmed by very low 2s values for both samples.Isotopic analyses were performed with the Carius tube isotope dilution procedure, using the PGE standard “WPR- 1” provided by the Canadian Certified Reference Materials Project.Isotopic data, in form of 187Os/188Os, were transformed into 187Os/186Os by using a 188Os/186Os ratio of 8,302 (Luck and Allegre, 1983). Initial 187Os/186Os ratios and gOs were determined by considering an age of emplacement of Luanga complex at 2700 Ma. Reliability of data is confirmed by very low 2s values for both samples.Our data were compared with those of other chromitites from layered complexes as Stillwater (A, B, G, I, K chromitites; Marcantonio et al., 1993) and Bushveld (UG1, UG2 chromitites; Hulbert and Gregoire, 1993) and PGE-rich Merensky Reef of Bushveld (Fig. 1).Luanga chromitites show high ratios, similar to those of Merensky Reef, and much higher than CHUR at 2700 Ma. It is possible to state that the mantle-melt system at Luanga underwent some modification and cannot be thought as due to a process of melting of a primary fertile undisturbed mantle. At this stage different processes able to increase (187Os/186Os)i can be envisaged: anomaly in the source due to the presence of a metasomatized mantle, strong differentiation during fractionation or crustal contamination.